14 – 36 ÷ (10 – 8)2 + 1

5 answers

Using the order of operations (PEMDAS/BODMAS), we first solve the expression inside the brackets:

(10 - 8)2 = 2^2 = 4

Now we can substitute this value back into the original expression:

14 - 36 ÷ 4 + 1

Next, we perform the division:

36 ÷ 4 = 9

Now we can substitute this value back into the expression:

14 - 9 + 1

Finally, we subtract and add:

14 - 9 + 1 = 6

Therefore, 14 – 36 ÷ (10 – 8)2 + 1 equals 6.
6^2 – 16 ÷ 4
Using the order of operations:

First, we perform the division:
16 ÷ 4 = 4

Now we can substitute this value back into the expression:
6^2 - 4

Next, we calculate the square:
6^2 = 36

Now we can substitute this value back into the expression:
36 - 4

Finally, we subtract:
36 - 4 = 32

Therefore, 6^2 – 16 ÷ 4 equals 32.
Simplify each expression. (1 pt. each)
5. 5(2x – 3)
6. -(6 – 11x)
7. 2x2 + 5xy + 3x2 – xy
8. 3(3x + 4y - 5) – 2x – 10y
5. 5(2x - 3) = 10x - 15

6. -(6 - 11x) = -6 + 11x

7. 2x^2 + 5xy + 3x^2 - xy = 5x^2 + 4xy

8. 3(3x + 4y - 5) - 2x - 10y = 9x + 12y - 15 - 2x - 10y = 7x + 2y - 15